INTERVENSI SOSIAL PADA ANAK REMAJA BERMAIN JUDI ONLINE - Aulia Setya Lestari; Jullyta Mirzania, Salwa Tazkia Fakhrezia, Yulita Gustinah, Mukhammad Bintang Juliano, Rijal Abdilah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This report discusses the phenomenon of online gambling among adolescents, which has grown rapidly due to technological advancements. The phenomenon is analyzed from various aspects, including the types of online gambling, the factors driving its increasing popularity, and the social, economic, and psychological impacts on adolescents. The report also evaluates government regulations and provides recommendations to minimize the negative impacts of this activity. The intervention was carried out using a group approach (mezzo), involving observation and interviews in the Jatiasih area. The results revealed that adolescents are drawn to online gambling due to its accessibility, promises of profit, and peer influence. The findings highlight patterns of addiction that lead to financial losses, stress, and social relationship damage. The mezzo technique proved effective in raising group awareness, despite initial resistance challenges. The report suggests an integrated approach involving families, educational institutions, and the government to create sustainable solutions